The The Effect of Quizizz Application and Youtube Video as Learning Media on Understanding Presentation Material with Learning Motivation as a Moderating Variable in Students of the Faculty of Economics and Business, Universitas Negeri Jakarta - Rahmadani, Ruli; Penga, Arnoldus Gian; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract.This study aims to analyze the effect from 119 students of the Faculty of Economics and Business, State University of Jakarta. The results of the analysis using PLS-SEM show that Quizizz and YouTube have a significant effect on material understanding This study aims to analyze the effect of using the Quizizz application and YouTube videos as learning media on students’ understanding of presentation material, with learning motivation as a moderating variable. Using an explanatory quantitative approach, data were collected through an online questionnaire, both directly and indirectly through learning motivation. Quizizz has a stronger influence than YouTube in increasing understanding and motivation. Learning motivation was shown to mediate the relationship between learning media and material understanding. These findings confirm the importance of integrating interactive and visual media in digital learning strategies to increase the effectiveness of student understanding. Keywords: Quizizz, YouTube, learning motivation, learning media, university students.